2006
DOI: 10.1590/s0100-67622006000500003
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho silvicultural de clones de eucalipto e características agronômicas de milho cultivados em sistema silviagrícola

Abstract: RESUMO -Com o objetivo de avaliar as respostas do eucalipto e do milho cultivados em sistemas silviagrícolas, implantou-se um experimento em Paracatu, MG, constituído por quatro clones de eucalipto (dois clones de Eucalyptus camaldulensis, códigos 137 e 180; dois clones de Eucalyptus urophylla, códigos 13 e 44), dispostos no espaçamento de 10 m x 4 m, consorciados nas entre linhas com a cultura do milho. Utilizou-se o delineamento experimental em blocos casualizados (DBC), com quatro tratamentos (quatro clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 3 publications
1
16
0
10
Order By: Relevance
“…Competition caused by the proximity of trees led to fewer oat plants establishing (P<0.05, Figure 4A) and was also reflected in the dry matter production, which increased with increasing distance from the trees (P<0.05, Figure 4B). In a similar study, maize cultivated between lines of 24-month old, 11-14 m tall eucalyptus trees spaced at 10 x 4 m grew at a density that was 24-39% of that observed when it was grown alone (MACEDO et al, 2006). Oat crop density also increased significantly with increasing distance from trees in the 'dehesas' of Spain -associations of 20-60 trees/ha and an herbaceous layer (MORENO et al, 2007).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Competition caused by the proximity of trees led to fewer oat plants establishing (P<0.05, Figure 4A) and was also reflected in the dry matter production, which increased with increasing distance from the trees (P<0.05, Figure 4B). In a similar study, maize cultivated between lines of 24-month old, 11-14 m tall eucalyptus trees spaced at 10 x 4 m grew at a density that was 24-39% of that observed when it was grown alone (MACEDO et al, 2006). Oat crop density also increased significantly with increasing distance from trees in the 'dehesas' of Spain -associations of 20-60 trees/ha and an herbaceous layer (MORENO et al, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…For that reason, the culm's capacity for storing excess photosynthate is critical for the period of grain filling (DIDONET et al, 2001;FANCELLI, 2003). Macedo et al (2006) observed lower weight, lower quality (lower cob size and poorly-formed grains) of corn cobs and lower grain yield in systems grown together with eucalyptus trees than in monocultures, and attributed the result to competition for light.…”
Section: Discussionmentioning
confidence: 93%
“…Dessa maneira, enquanto o milho em monocultivo apresentava plantas em toda a parcela, a cultura semeada nas entrelinhas das árvores tinha uma redução de aproximadamente 25% da área efetiva, devido à presença do componente arbóreo. Resultados semelhantes foram obtidos por MACEDO et al (2006), em cultivo consorciado do milho com clones de eucalipto com 24 meses plantados no espaçamento 10x4m.…”
Section: Resultsunclassified
“…Em outro trabalho, MACEDO et al (2006) compararam a produção média de grãos de milho cultivado em monocultivo com a produção em sistemas consorciados com clones de eucalipto com 24 meses e observaram redução na produção média nesses sistemas consorciados de 81,04, 69,69, 58,85 e 58,62%, respectivamente, nos consórcios com os clones 137 de Eucalyptus camaldulensis, 13 de E. urophylla, 180 de E. camaldulensis e 44 de E. urophylla, implantados no espaçamento 10 x 4m. A produção média de grãos de milho, obtida nas linhas distanciada entre 1,8 e 2,7m das linhas de plantio de eucalipto, apresentou redução de 29,68% em relação à produção média de grãos de milho, obtida nas linhas de plantio mais distantes das árvores de eucalipto (entre 4,5 e 5,4m de distância), provavelmente devido ao maior tempo de sombreamento nas plantas de milho localizadas mais próximas das linhas de plantio de eucalipto.…”
Section: -----Estande (Plantas Ha -¹) ----------Alturas De Plantas (Munclassified
See 1 more Smart Citation